2013
DOI: 10.1093/occmed/kqt037
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injuries from work accidents: a retrospective study

Abstract: Occupational TBI requiring hospitalization is most frequently due to falls and falling objects, with potentially grave consequences. This study further highlights the urgent need to implement preventative measures to improve construction worker safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 8 publications
3
10
0
1
Order By: Relevance
“…Seven studies presented data on the severity of wrTBI cases, assessed using measures such as the Glasgow Coma Scale (GCS), Injury Severity Score (ISS), and duration of loss of consciousness and/or post‐traumatic amnesia. Specifically, two studies using hospital records showed that the majority (>70%) of hospitalized wrTBI cases were mild (i.e., GCS 13–15) [Kraus and Fife, ; Salem et al, ], while studies using trauma registry data had more severe cases as defined by the ISS [Kim et al, ; Graves et al, ]. In nine studies, the percentage of fatal cases (i.e., case fatality rates) ranged from 4% to 11%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies presented data on the severity of wrTBI cases, assessed using measures such as the Glasgow Coma Scale (GCS), Injury Severity Score (ISS), and duration of loss of consciousness and/or post‐traumatic amnesia. Specifically, two studies using hospital records showed that the majority (>70%) of hospitalized wrTBI cases were mild (i.e., GCS 13–15) [Kraus and Fife, ; Salem et al, ], while studies using trauma registry data had more severe cases as defined by the ISS [Kim et al, ; Graves et al, ]. In nine studies, the percentage of fatal cases (i.e., case fatality rates) ranged from 4% to 11%.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, falls were more common in older workers [Kim et al, ; Colantonio et al, , 2010; Wei et al, , 2012] and were the leading cause of fatal wrTBI among those aged 55 years and above [Tiesman et al, ]. Of all hospitalized/fatal cases of wrTBI due to falls, the majority (>80%) involved falls from an elevation [Heyer and Franklin, ; Cohen et al, ; Wrona, ; Salem et al, ], while falls from the same level were more common among nonfatal and less severe cases [Colantonio et al, ; Wei et al, ; Liu et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…The main factors leading to falls were the type of floor (slippery, uneven surfaces) and outdoor environments. In the United Arab Emirates, falls accounted for 63% of cases of occupational traumatic brain injury in patients of a hospital, showing the importance of implementing preventive measures (14) .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on traumatic brain injuries admitted to an Abu Dhabi Hospital, falling objects counted for 34% of the injuries (Salem, Jaumally, Bayanzay, Khoury, & Torkaman, 2013). Falling objects can cause injuries having prolonged hospitalisation and/or a permanent disability resulting in substantial cost to the healthcare system.…”
Section: Introductionmentioning
confidence: 99%